Kajian Pengajaran Bahasa Inggris dengan Code Switching oleh Guru-Guru SD di Bawah Yayasan Pendidikan Islam Al-Falah Semarang - Suwarti, Tarcisia Sri; Lestari, Siti; Widiyanto, Muhammad Wahyu (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
The ability to speak English can make a person more superior and have the opportunity to compete in the future, mastery requires Indonesian as an intermediary language to facilitate the introduction of the language. The elementary school level is the basic stage of mastering English. The study of English teaching with code switching needs to be done as an effort to find out the ongoing teaching process and its situation. This research method is a descriptive qualitative with the research subjects of elementary school teachers under the Al-Falah Islamic Education Foundation Semarang. The stages of the research method are through data collection (observation, questionnaire and interview). Based on the results of the study, it can be concluded that English Teaching with code switching by teachers occurs in the pre-activities, main-activities and post-activities in the classroom and most occur during the exploration of material, elaboration of material and drawing conclusions; Teachers use code switching to clarify vocabulary and material, especially new material, to represent the expression to be conveyed especially when it is difficult to find a word equivalent, as well as to maintain the use of Indonesian for teachers and students; The obstacles faced are the limitations between teaching time and the target material taught by the teacher. For this reason, the teacher must be able to manage time and organize the use of code switching techniques in a timely manner.